225 - COMPARATIVE ANALYSIS OF RECTUS ABDOMINAL MUSCLE MYOELECTRIC ACTIVATION IN THE COLUMN FLEXION ON STABLE AND NON STABLE SURFACES- A PILOT SUTDY (Fiep Bulletin - online, 2011)
Nowadays physical exercises in labile surfaces have been preconized by the belief that this kind of exercises will provide an increase on trunk muscle activity and other benefits therefore scientific studies are controversial about this subject, and consequently there are doubts about the achieved results. According to this the aim of the study was to analyze through comparative electromyography the abdominal exercise in stable and labile surfaces using contraction peak. 5 healthy volunteers have participated on this pilot research and every volunteer realized an anamnesis and after that and anthropometric evaluation to sample characterization. After the anthropometric evaluation all volunteers were submit to skin preparation and then 2 bipolar electrodes were implanted on each surface of rectus abdominal muscle to EMG analysis. The volunteers realized the exercise during 40seconds in both surfaces accounting 10 repetitions. A 30º trunk curl angle was limited on the concentric phase to exercise execution. The medium values of the obtained data of exercise execution in both surfaces were compared through test T for dependent sample and the results demonstrate that the abdominal exercise in labile surface showed significant statistic difference when compared to the exercise in stable surface with value of p=0,000000. According to this the abdominal exercise in labile surfaces seems to be more efficient when peak contraction is considered, a important factor to a strength training prescription.
Keywords: abdominal exercises; stable surfaces; labile surfaces; electromyography